NRG Oncology Survey on Practice and Technology Use in SRT and SBRT Delivery - Chetvertkov, Mikhail; Monroe, James Ira; Boparai, Jaskaran; Solberg, Timothy D.; Pafundi, Deanna H.; Ruo, Russell L.; Gladstone, David J.; Yin, Fang-Fang; Chetty, Indrin J.; Benedict, Stanley; Followill, David S.; Xiao, Ying; et al. (Frontiers in Oncology, 2020)
Purpose: To assess Stereotactic Radiotherapy (SRT)/Stereotactic Body Radiotherapy (SBRT) practices by polling clinics participating in multi-institutional clinical trials. Methods: The YYYY distributed a survey consisting of 23 questions, which covered general technologies, policies, and procedures used in the Radiation Oncology field for the delivery of SRT/SBRT (9 questions), and site-specific questions for brain SRT, lung SBRT, and prostate SBRT (14 questions). Surveys were distributed to 1,996 radiotherapy institutions included on the membership rosters of the five YYYY clinical trial groups. Patient setup, motion management, target localization, prescriptions, and treatment delivery technique data were reported back by 568 institutions (28%). Results: 97.5% of respondents treat lung SBRT patients, 77.0% perform brain SRT, and 29.1% deliver prostate SBRT. 48.8% of clinics require a physicist present for every fraction of SBRT, 18.5% require a physicist present for the initial SBRT fraction only, and 14.9% require a physicist present for the entire first fraction, including set-up approval for all subsequent fractions. 55.3% require physician approval for all fractions, and 86.7% do not reposition without x-ray imaging. For brain SRT, most institutions (83.9%) use a PTV margin of 2 mm or less. Lung SBRT PTV margins of 3 mm or more are used in 80.6% of clinics. VMAT is the dominant delivery method, in 62.8% of SRT treatments, 70.9% of lung SBRT, and 68.3% of prostate SBRT. Conclusion: This report characterizes SRT/SBRT practices in radiotherapy clinics participating in clinical trials. Data made available here allows the radiotherapy community to compare their practice with that of other clinics, determine what is achievable, and assess areas for improvement.